1984
DOI: 10.1111/j.1651-2227.1984.tb09958.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Meningitis in Nigerian Infants

Abstract: 53 Nigerian infants with neonatal meningitis were prospectively studied. The striking features were: (a) the higher predisposition (26.7-fold) of LBW infants to developing meningitis than has been previously reported in the literature; (b) the predominant role of E. coli and Staphylococcus aureus; and (c) the rarity of salmonella organisms and the conspicuous absence of group B streptococcus as aetiological pathogens. The outcome was related to the age of onset and type of micro-organism. The presence of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 10 publications
4
27
0
Order By: Relevance
“…Staph. aureus accounted for 55.5% of the gram positive organisms and is comparable to reports from Nigeria [8]. The incidence of pneumococcal meningitis (5.3%) was low compared to that reported in South African infants (25%) [9].…”
Section: Neonatal Bacterial Meningitis In North Africasupporting
confidence: 80%
See 3 more Smart Citations
“…Staph. aureus accounted for 55.5% of the gram positive organisms and is comparable to reports from Nigeria [8]. The incidence of pneumococcal meningitis (5.3%) was low compared to that reported in South African infants (25%) [9].…”
Section: Neonatal Bacterial Meningitis In North Africasupporting
confidence: 80%
“…Lowbirth-weight infants had 10.1 times higher risks to develop meningitis (16.6 per 1000) than full-term newborns (1.64 per 1000). The overall incidence of 1.97 per 1000 live births was higher than fig- ures reported from Nigeria (0,69 per 1000) [8] and North America (0.4-0.46 per 1000) [6,11]. The higher incidence may be due to the increased number of high-risk births (20.6%) [10] and nosocomial infections with Klebsiella.…”
Section: Neonatal Bacterial Meningitis In North Africamentioning
confidence: 48%
See 2 more Smart Citations
“…5 Reports from poor and developing countries, like Nigeria and Ethiopia, showed Gram negative organisms, such as E. coli, Klebsiella, and Enterobacter were the top agents that cause neonatal meningitis. 12,13 In other developing countries, such as Panama and Haiti, although Gram negative organisms (E. coli, Klebsiella, Enterobacter, Serratia, and Pseudomonas) were still in the top charts for causing neonatal meningitis, the incidence of GBS infection tends to increase. 14,15 All studies above reported the same results, organisms that cause sepsis are almost identical with organisms that cause meningitis.…”
Section: Discussionmentioning
confidence: 99%